The Use of Instructional Video Media to Increase The Motivation to Learn Mathematics in Grade II SDN 1 Bobotsari - Iin Setalasiah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Media is an important component in increasing student motivation. The purpose of this study was to increase the learning motivation of students in learning mathematics using video media. This research is a classroom action research (PTK) which is conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 25 students of class II SD Negeri 1 Bobotsari, totaling 25 students. The research instrument was the observation sheet and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The finding of this study is that the use of instructional video media can increase students' learning motivation in mathematics learning of students on the equivalent of currency values in class II SD Negeri 1 Bobotsari. The results of the study were indicated by an increase in the learning motivation of students in the first cycle 40%, in the second cycle it increased to 92